FM1-2 A prospective study on surgical management of foot deformities in charcot marie tooth disease. Issue 3 (14th February 2019) - Laura, M; Ramdharry, G; Singh, D; Kozyra, D; Skorupinska, M; Reilly, M
Abstract : Objectives: Charcot-Marie-Tooth (CMT) Disease is the most common inherited peripheral neuropathy. Foot deformities are frequently observed in CMT patients and orthopaedic surgery is often required. Currently the evidence base on surgical management is limited. We prospectively studied surgical management of CMT patients attending our centre. Subjects: Patients were assessed at baseline and yearly after surgery. Methods: Assessment and data included: history of ankle instability, pain, skin condition, lower limb strength assessment, Charcot-Marie-Tooth Examination Score, Foot Posture Index, ankle dorsiflexion range of movement, questionnaires, details of surgical procedures. Results: 29 feet in 24 CMT patients (17 males, 7 females, mean age: 38.6±13) were evaluated prior to surgery. All patients but one had genetically confirmed CMT (18 CMT1A; 4 CMTX; 1 CMT4A). 17 feet in 12 pts were evaluated after 1 year; 10 feet in 9 pts were evaluated after 2 years; 8 feet in 7 pts were evaluated after 3 years. A wide range of surgical procedures were performed by one dedicated orthopaedic surgeon. There was significant improvement of foot alignment (p<0.001), callosities (p=0.002) and pain (p=0.022) after surgery. Surgery had no significant effect on strength, ankle range of movement, falls and fatigue. Conclusions: The findings showed significant improvement of foot alignment, callosities and pain after surgery. Data acquired from this study will help developing orthopaedic intervention guidelines and identify areas for further research.